Production of biodiesel from waste cooking oil using mesoporous MgO-SnO2 nanocomposite - Amirthavalli Velmurugan; Anita R. Warrier (Journal of Engineering and Applied Science, 2022)
Abstract Mesoporous, bifunctional MgO-SnO2 nanocatalysts with enhanced surface area are used for producing biodiesel from waste cooking oil. Biodiesel with yield of 80% is achieved within the first 20 min when transesterification is carried out at an optimum condition of 18:1 methanol to oil ratio, 2 wt% of nanocatalyst, and at a reaction temperature of 60 °C. The conversion gives a maximum yield of 88% when transesterification is allowed to continue for 120 min. The waste cooking oil used in this work is dominated with linoleic acid and oleic acid, which during transesterification gets converted into methyl linoleate and 9-octadecenoic acid methyl ester. These nanocatalysts are fabricated using a composite of rutile (tetragonal) phase SnO2 and cubic phase MgO nanostructures with prominent crystal orientation along [211] and [200] plane respectively. The MgO-SnO2 nanocomposites with an enhanced surface area of 31 m2/g, basic sites of 2 mmol/g, and particle size of ~15 nm are synthesized by novel sequential thermal decomposition and sol-gel technique. The synthesized wide band gap nanocomposites have Mg and Sn in the ratio of 15:1 and do not have any impurity phases as observed in the X-ray diffraction pattern and EDS spectrum. The presence of surface oxygen states and Mg2+ and Sn4+ oxidative states is responsible for the catalytic activity and recyclability displayed by the composites. This work signifies the role of nanocomposites and their synthesis conditions in improving the rate of transesterification. These metal oxide nanocomposites which are nontoxic, stable, cost effective, and easier to synthesis are promising catalysts for large-scale transesterification of waste cooking oil to biodiesel.